The Impact of a Health-run on Remittances and Financial Inclusion - Sunday Agbor Mbu; Maurice Ayuketang Nso (European Scientific Journal, ESJ, 2021)
The study examines the impact of health runs or crises on financial remittances and inclusion. Data were collected through a survey questionnaire administered to a sample of 60 respondents made up of financial services employees and users of financial services, irrespective of their age and years of trade experience. Results show that remittances and financial inclusion levels should be affected adversely due to the coronavirus ( COVID-19) health run. The magnitude of the negative effect of a health crisis on financial remittances and inclusion as measured by the correlation matrix is strong, but comparatively the same for the assessed variables. Our findings reveal that a severe global health crisis would force an exponential decline in remittances and financial inclusion. Findings further reveal that there exists no relationship between financial remittances and financial inclusion under a health crisis. The study here recommends measures policymakers can use to boast financial flows and inclusion during a period of a severe global health crisis.